Cocoa Pod Husk Carbon Family for Biogas Upgrading: Preliminary Assessment Using the Approximate Adsorption Performance Indicator - Khaled Abou Alfa; Diana C. Meza-Sepulveda; Cyril Vaulot; Jean-Marc Le Meins; Camelia Matei Ghimbeu; Louise Tonini; Janneth A. Cubillos; Laurent Moynault; Vincent Platel; Diego Paredes; Cecile Hort (C)
The preliminary selection of adsorbents for the separation of a gas mixture based on pure gas adsorption remains a critical challenge; thus, an approximate adsorption performance indicator (AAPI) was proposed for the initial evaluation of the adsorbents to separate the biogas main constituents (carbon dioxide/methane (CO2/CH4)) by studying their pure gas adsorption. Three samples derived from cocoa pod husk (CPH), namely Cabosse-500 (pyrolyzed at 500 °C), Cabosse-700 (pyrolyzed at 700 °C), and Cabosse-A-700 (activated with CO2 at 700 °C), were synthesized, characterized, and evaluated for the pure gases adsorption. This study presents an AAPI evaluation, which takes into account adsorption capacity, approximate selectivity, and heat of adsorption. Adsorption isotherms indicate the ability of the CPH family to selectively capture CO2 over CH4, as they have a high approximate selectivity (>1) thanks to their physical properties. Changing the pyrolysis temperature, activation methods, and varying the pressure can significantly change the choice of the most effective adsorbent; Cabosse-A-700 showed better performance than the other two in the low and high pressure range owing to its presence of micropores and mesopores, which enhances the CO2 adsorption and therefore the AAPI.